Pendampingan dan Edukasi Restorative Justice dalam Penanganan Tindak Pidana Berbasis Digital di Masyarakat - Januri; Mirwansyah; Irwan Jaya Diwirya (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2025)
The rapid development of information and communication technology has significantly transformed social interaction and economic activities, while simultaneously increasing the incidence of digital-based criminal acts such as online fraud, defamation on social media, dissemination of hoaxes, and illegal access to personal data. Limited digital legal literacy causes many community members to become involved in criminal cases without fully understanding the legal consequences of their actions. In response to this condition, this community service program aims to provide assistance and legal education on restorative justice as an alternative approach in handling digital-based criminal offenses. The program was implemented through legal counseling, interactive discussions, case simulations, and community-based mentoring tailored to the characteristics of the target community. The results show a measurable increase in participants’ understanding of digital criminal law and restorative justice principles, as indicated by pre-test and post-test evaluations and positive participant feedback. The program also produced educational materials and a practical mentoring model that can be replicated in other communities. Overall, the implementation of restorative justice education contributes to enhancing legal awareness, encouraging proportional conflict resolution, and promoting a more humane and restorative approach to digital crime handling within the community.